2020
DOI: 10.1016/j.jid.2019.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Cancers in Patients with Invasive and In Situ Squamous Cell Skin Carcinoma, Kaposi Sarcoma, and Merkel Cell Carcinoma: Role for Immune Mechanisms?

Abstract: Second primary cancers (SPCs) are becoming a common cancer entity, which may interfere with survival in relatively benign first primary cancers. We examined the hypothesis that immune dysfunction may contribute to SPCs by assessing SPCs associated with known immune responsive skin cancers, invasive and in situ squamous cell carcinoma, Kaposi sarcoma, and Merkel cell carcinoma. Cancers were identified from the Swedish Cancer Registry from the year 1958 to 2015. Standardized relative risks were calculated bidire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…14 Possible causes or contributing factors for SPCs are many, but probably the most important ones are intensive medical surveillance after the diagnosis of FPC, therapy for FPC, shared genetic or non-genetic risk factors between FPC and SPC and immune dysfunction elicited by FPC. 2,18,19 In the case of skin cancer therapy is not an issue, but medical surveillance probably is, because SPCs were diagnosed relatively shortly after skin cancers (2-3 years) which are generally diagnosed in elderly subjects (median diagnostic ages were 78-82 years in this study). 20 However, as practically all cancers reported to the Swedish Cancer Registry are histologically confirmed, the effect of medical surveillance would be antedating of diagnoses rather than introducing wrong diagnoses.…”
Section: Dovepressmentioning
confidence: 84%
“…14 Possible causes or contributing factors for SPCs are many, but probably the most important ones are intensive medical surveillance after the diagnosis of FPC, therapy for FPC, shared genetic or non-genetic risk factors between FPC and SPC and immune dysfunction elicited by FPC. 2,18,19 In the case of skin cancer therapy is not an issue, but medical surveillance probably is, because SPCs were diagnosed relatively shortly after skin cancers (2-3 years) which are generally diagnosed in elderly subjects (median diagnostic ages were 78-82 years in this study). 20 However, as practically all cancers reported to the Swedish Cancer Registry are histologically confirmed, the effect of medical surveillance would be antedating of diagnoses rather than introducing wrong diagnoses.…”
Section: Dovepressmentioning
confidence: 84%
“… 29–31 An increased risk of GC as SPC has been found in studies analyzing SPCs after NHL and skin SCC. 32 , 33 It was also shown that family history of GC increased the likelihood of second GC in NHL patients. 34 We thus consider plausible that the increased risk for second GCs after skin SCC and NHL may have an immunological component.…”
Section: Discussionmentioning
confidence: 99%
“…Plausible etiologies for SPCs are many, but probably the most important ones are intensive medical surveillance (surveillance bias) after the diagnosis of the first primary cancer (FPC), therapy for FPC, shared genetic or nongenetic risk factors between FPC and SPC, and immune dysfunction elicited by FPC, or interactions between these [10] , [11] , [12] . As data on the possible risk factors for SPCs are usually limited, we have devised a bidirectional analysis as a tool to help interpret the findings [11] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%